2018
DOI: 10.18632/oncotarget.24506
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of autophagy-related genes during the adipocyte differentiation using public-access data

Abstract: Autophagy contributes to reorganizing intracellular components and forming fat droplets during the adipocyte differentiation. Here, we systematically describe the role of autophagy-related genes and gene sets during the differentiation of adipocytes. We used a public dataset from the European Nucleotide Archive from an RNA-seq experiment in which 3T3-L1 cells were induced by a differentiation induction medium, total RNA was extracted and sequenced at four different time points. Raw reads were aligned to the UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Lipophagy is the selective removal of lipid droplets in cytosolic organelles by lysosomes, which are derived from stimulated autophagy markers such as LC3 and p62 (Singh and Cuervo, 2012; Ward et al, 2016). Lipogenesis, often considered identical to adipogenesis, is focused on the formation of lipid droplets during white adipocyte differentiation with autophagy activation; lipolysis, on the other hand, is the secretion of glycerol and fatty acid partially resulting from the degradation of lipid droplets by autophagy (Cingolani and Czaja, 2016; Ahmed et al, 2018). The balance between lipogenesis and lipolysis plays a vital role in regulating the lipid metabolism in white and brown adipocytes (Singh and Cuervo, 2012; Martinez-Lopez et al, 2016; Zechner et al, 2017).…”
Section: Lipophagy In Adipocyte Lipid Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Lipophagy is the selective removal of lipid droplets in cytosolic organelles by lysosomes, which are derived from stimulated autophagy markers such as LC3 and p62 (Singh and Cuervo, 2012; Ward et al, 2016). Lipogenesis, often considered identical to adipogenesis, is focused on the formation of lipid droplets during white adipocyte differentiation with autophagy activation; lipolysis, on the other hand, is the secretion of glycerol and fatty acid partially resulting from the degradation of lipid droplets by autophagy (Cingolani and Czaja, 2016; Ahmed et al, 2018). The balance between lipogenesis and lipolysis plays a vital role in regulating the lipid metabolism in white and brown adipocytes (Singh and Cuervo, 2012; Martinez-Lopez et al, 2016; Zechner et al, 2017).…”
Section: Lipophagy In Adipocyte Lipid Metabolismmentioning
confidence: 99%
“…Adipogenesis is a unique adipocyte differentiation process that generates lipid droplets with triglycerides and fatty acids inside the lipid vacuoles (Rosen and Spiegelman, 2006; Ro et al, 2013; Ahmed et al, 2018). Autophagy for non-selective bulk degradation of proteins and lipids through the fusion of autophagosomes and lysosomes is suggested as one of the major types of autophagy in adipocytes (Singh et al, 2009b; Singh and Cuervo, 2012; Ro et al, 2013).…”
Section: Introduction: Autophagy In Adipocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, this process likely involves a wide range of changes in transcription, translation and protein modification. In a previous study from our laboratory, we suggested that many autophagy genes were functionally associated with adipocyte differentiation using the RNA-Seq expression data [ 19 ]. We also showed that the mRNA level of key autophagy genes is specifically regulated at different time points, and clusters of these genes respond to the differentiation stimulus in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…3T3-L1 pre-adipocytes were cultured and induced for differentiation using MDI protocol as described before [ 19 ]. Total RNA was collected at four different time points corresponding the the major differentiation stages of the adipocytes (−2 day, full confluence; 0 day, undifferentiated; 10 h differentiating; and −6 day, maturating).…”
Section: Methodsmentioning
confidence: 99%